Geoinformation technology for natural disaster management and rehabilitation : Proceedings of 2 nd International Conference 1-2, December 2008, Bangkok, Thailand - Tripathi, Nitin Kumar (editor) (Pathumthani:Geoinformatics International Co. Ltd., 2008)
Koleksi Referensi (Tidak Dipinjamkan)